Resource Intensity for Children and Youth: The Development of an Algorithm to Identify High Service Users in Children's Mental Health. - Stewart, Shannon L; Poss, Jeff W; Thornley, Elizabeth; Hirdes, John P (Health Services Insights, 2019)
Children's mental health care plays a vital role in many social, health care, and education systems, but there is evidence that appropriate targeting strategies are needed to allocate limited mental health care resources effectively. The aim of this study was to develop and validate a methodology for identifying children who require access to more intense facility-based or community resources. Ontario data based on the interRAI Child and Youth Mental Health instruments were analysed to identify predictors of service complexity in children's mental health. The Resource Intensity for Children and Youth (RIChY) algorithm was a good predictor of service complexity in the derivation sample. The algorithm was validated with additional data from 61 agencies. The RIChY algorithm provides a psychometrically sound decision-support tool that may be used to inform the choices related to allocation of children's mental health resources and prioritisation of clients needing community- and facility-based resources.